Investigation of mechanical field weakening of axial flux permanent magnet motor - Syaifuddin Mohd, M. (Institute of Physics Publishing, 2015)
An investigation of axial flux permanent magnet motor (AFPM) characteristics was conducted with a proposed mechanical field weakening control mechanisms (by means of stator-rotor force manipulation) on the motor through modeling and experimentation. By varying the air gap between at least two bistable positions, the peak torque and top speed of the motor can be extended. The motor high efficiency region can also be extended to cover greater part of the motor operating points. An analytical model of the motor had been developed to study the correlation between the total attraction force (between the rotor and the stator) and the operating parameters of the motor. The test results shows that the motor output complies with the prediction of the research hypothesis and it is likely that a spring locking mechanism can be built to dynamically adjust the air gap of the motor to increase the operating range and could be applied in electric drivetrain applications to improve overall efficiency of electric and hybrid electric vehicles.